2003
DOI: 10.1128/iai.71.9.4831-4841.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Cycle of Cryptococcus neoformans var. grubii and Virulence of Congenic a and α Isolates

Abstract: Cryptococcus neoformans is a human-pathogenic fungus that has evolved into three distinct varieties that infect most prominently the central nervous system. A sexual cycle involving haploid cells of a and ␣ mating types has been reported for two varieties (C. neoformans var. neoformans, serotype D, and C. neoformans var. gattii, serotypes B and C), yet the vast majority of infections involve a distinct variety (C. neoformans var. grubii, serotype A) that has been thought to be clonal and restricted to the ␣ ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
312
4
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 381 publications
(331 citation statements)
references
References 63 publications
10
312
4
5
Order By: Relevance
“…Whereas Gpa1 is known to function in a conserved cAMP signaling pathway, functions of Gpa2 and Gpa3 remain unreported. We have recently identified a regulator of the G protein signaling protein, Crg1, as one of the key regulators for mating and virulence in C. neoformans (51,52) and have shown that Crg1 functions as a GTPase activating protein specific to Gpa2. 4 To expand our studies on regulators of G protein signaling, we performed a yeast two-hybrid screen using Gpa1 as bait.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas Gpa1 is known to function in a conserved cAMP signaling pathway, functions of Gpa2 and Gpa3 remain unreported. We have recently identified a regulator of the G protein signaling protein, Crg1, as one of the key regulators for mating and virulence in C. neoformans (51,52) and have shown that Crg1 functions as a GTPase activating protein specific to Gpa2. 4 To expand our studies on regulators of G protein signaling, we performed a yeast two-hybrid screen using Gpa1 as bait.…”
Section: Resultsmentioning
confidence: 99%
“…Mating assays: Mating assays were conducted as described previously (Nielsen et al 2003). Briefly, strains were pregrown on YPD plates for 2 days, after which a small amount of cells was removed using a flat-end toothpick and patched onto V8 and MS mating media (pH 5.0) either alone or mixed in equal proportions with a strain of the opposite mating-type (MAT ) (Kwon-Chung et al 1982;Xue et al 2007).…”
Section: Strains and Mediamentioning
confidence: 99%
“…grubii) by a slide agglutination test (Crypto-Check kit, Iatron) and mating type a by PCR with specific primers that amplify portions of the STE20a or STE20a allele (Nielsen et al, 2003). We determined the LD 50 for each of the isolates at 15 days following the intracranial (i.c.)…”
Section: Neoformans Isolates Recovered From the Csf Of Persons Witmentioning
confidence: 99%